Corporate Strategies in the Global Era: The Case of Mega-hog Farms in the Texas Panhandle Region - Bonanno , Alessandro; H. Constance, Douglas (The International Journal of Sociology of Agriculture and Food, 2021)
Employing the case of the expansion of mega-hog operations in Texas Panhandle region, this paper illustrates relevant strategies that agro-food transnational corporations (TNCs) employ to maximize capital accumulation and address locally-based resistance. Salient literature on socioeconomic trends in the global era underscores that through hyper-mobility and by pitting localities against each other, TNCs take advantage of communities’ desires to attract external investments to stimulate local growth. This literature also points out that the growth of TNCs creates limits for the maintenance of democracy. The events of the case indicate that agro-food TNCs moved to the Texas Panhandle region to capitalize on favorable socio-political conditions. However, anti-corporate local resistance developed on the grounds that newly created mega-hog operations contaminated the environment and exacerbated social problems in the area. TNCs responded by adopting postures which transcended hyper-mobility strategies and involved actions at the legitimative, political and economic levels. At the legitimative level, TNCs presented an image which stressed conformity to existing environmental regulations, narrowed the definition of environmentally sound agricultural activities and delegitimized opposition. At the political level, TNCs were able to control local environmental agencies and depoliticize environment evaluation procedures. Economically, growth, the creation of new jobs, but also large monetary donations to communities, were all employed to solicit acceptance of corporate postures. The paper concludes with some brief reflections on the impact that the development of TNCs has on democracy.